2015
DOI: 10.1055/s-0035-1564131
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Blood Pressure and Normal Range Thyroid Function Tests in a Population Based Tehran Thyroid Study

Abstract: Several studies have shown an association between overt hypothyroidism and diastolic hypertension. Association between subclinical hypothyroidism and hypertension is a matter of debate. The aim of this study was to examine the association of systolic and diastolic blood pressure, pulse pressure and mean arterial blood pressure with serum thyroid hormones levels in euthyroid subjects.Data from 4 756 individuals of the Tehran Thyroid study (TTS) without any previously known thyroid disease were analyzed. We divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…On the other hand, results of the present study showed that in the RR, serum FT4 exerts more notable effects on BP, especially SBP, compared to serum TSH. This reciprocal finding regarding the effect of serum TSH and FT4 has been observed in several cross-sectional [23,27] and cohort studies extracted from TTS data [28] also other surveys [29]. It is suggested that FT4 is a more reliable index for evaluation of thyroid function at the cellular levels; moreover, TSH changes following deviations in serum levels of FT4 is less vigorous whenever deviations are minimal [30].…”
Section: Total Populationsupporting
confidence: 53%
See 1 more Smart Citation
“…On the other hand, results of the present study showed that in the RR, serum FT4 exerts more notable effects on BP, especially SBP, compared to serum TSH. This reciprocal finding regarding the effect of serum TSH and FT4 has been observed in several cross-sectional [23,27] and cohort studies extracted from TTS data [28] also other surveys [29]. It is suggested that FT4 is a more reliable index for evaluation of thyroid function at the cellular levels; moreover, TSH changes following deviations in serum levels of FT4 is less vigorous whenever deviations are minimal [30].…”
Section: Total Populationsupporting
confidence: 53%
“…Thyroid function has complex direct and indirect effects on BP and several mechanisms have been speculated for explaining the role of thyroid hormones in BP regulation [19]. Data about changes in BP across the spectrum of thyroid dysfunction is well documented; but evidence regarding these changes across the range of euthyroidism is conflicting in view of cross-sectional studies [20][21][22][23] and very scarce and inconsistent in longitudinal surveys. Moreover, none of them have considered serum thyroid hormones; herein, we present an overview on the main results of the longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicates that people with higher serum TSH level within normal range had elevated BP than those with lower serum TSH level in normal range [32]. However, another study from 4,985 euthyroid individuals reveals that there is no association in between serum TSH and BP [34]. In our study, results showed serum TSH had positive relationship with SBP and DBP.…”
Section: Discussioncontrasting
confidence: 46%
“…47 In contrast to the positive association between fT4 and AF, we did not find an association between TSH levels in the reference range and AF, and this pattern of a positive association between fT4 but not TSH values in the reference range has also been shown for other adverse cardiac outcomes including congestive heart failure 14 and sudden cardiac death, 15 as well as for blood pressure. 48 These results of the effect of normal thyroid function on the heart are in contrast to the findings of a statistically significant inverse association between TSH levels within the reference range and dementia, whereas no significant association between fT4 levels in the normal range and rates of dementia was found in this study, 14 suggesting that thyroid hormone metabolism and action differs between target organs such as the heart and brain because of differences in deiodinase activity and thyroid hormone receptor expression; 47 these differences may explain why some clinical phenotypes are associated with fT4 only, some with TSH only, and others with both. These findings are also consistent with the observation that fT4 concentrations may differ even among euthyroid persons with the same TSH values: 49 individuals with higher fT4 values have higher cardiac exposure to thyroid hormones and are consecutively at a higher risk of AF, which is reflected by the findings of our study.…”
Section: Discussionmentioning
confidence: 99%